Detección de marcadores microsatélites asociados con la resistencia al añublo bacterial de la yuca (Manihot esculenta Crantz) en Colombia - Hurtado López, P.X.; Álvarez, E.; Llano Rodríguez, Germán Alberto; Fregene, Martin A. (2004)
A major strategy for managing Cassava Bacterial blight (CBB), caused by Xanthomonas axonopodis pv. manihotis, is to use varietal resistance, that is, to develop cassava varieties with lasting genetic resistance. A search for the genes that dominate resistance to the disease was initially conducted by seeking the molecular markers associated with the plant s phenotypic response to CBB. The response in four BC1 (backcross 1) cassava families was accordingly evaluated under natural disease pressure at Villavicencio (Meta, Colombia). The most segregating family was then selected, and its response to CBB was verified under greenhouse conditions at CIAT (Palmira, Valle). Family GM 315 presented the best segregation, so, it was the most suitable for seeking association between its phenotypic reaction and the presence of a molecular marker. Of 486 microsatellite primers evaluated by bulked segregant analysis (BSA), 17 showed polymorphism among contrasting groups. Only one primer, SSRY 65, showed significant differences between resistant and susceptible individuals. On evaluating this primer for the entire segregating family, an association was found between its presence and individuals evaluated phenotypically as resistant in the field and greenhouse (minimum P = 0.0015 and P = 0.007, respectively, in a chi-square test of independence). With the results of the statistical analysis, the predictive values, specificity, and sensibility of marker SSRY 65 were calculated. The positive predictive values generated indicate that this marker can be used in diagnostic tests to detect the presence of a specific band in resistant individuals of families genetically related to the GM 315 family.